As tramas do poder e seus reflexos no discurso feminino do início do século XX em Maria da Tempestade (1956), de João Mohana - ALMEIDA, Maristela dos Santos (2019)
Maria da Tempestade (1956), a novel written by author João Mohana, who was born in Maranhão, reveals the context of a time when the traditional family values were prioritized over the ideals of affective freedom and independence. Bárbara, the main character of this piece of literature work, presents herself as a woman ahead of her time, since she demonstrates the desires and ideals which are not perceived as common attributes of a woman from the beginning of the twentieth century. In the beginning of the said century, ideals which aimed to expand women’s rights were part of the speeches in circulation. Simone de Beauvoir (2016) and other authors – not to mention the activists – were part of a scenario of protests which tried to guarantee greater participation of women in social life. Immersed in this confrontation scenario, three characters – three feminine souls – stablish relationships of power that conflict with one another. According to philosopher Michel Foucault, the idea of relations of powers is based on the study of mechanisms that produce ideals, words, and actions. In order to exercise a power through subtle mechanisms, it is necessary to organize, form, and put a knowledge into circulation (FOUCAULT, 2003). With that in mind, this work aims to discuss how the relations between Bárbara, her mom, Elisa, and the lady with a decadent life, Cora Mendes, stablish relations that convey power, besides influencing the constitution of its respective subjectivities. For this purpose, the studies of Michel Foucault, as well as some concepts of analysis of speech will be used to achieve a better understanding of the discursive formation and the production of the senses that are circulating in the beginning of the twentieth century, period that the mentioned narrative is situated. To assure an approximation between Literature and Analysis of Speech, we will mobilize the researches made by Dominique Maingueneau about the Literary Speech. According to Maingueneau, the field of study of a literary production is constituted by a “system whose many instances interact: the text genre, intertextuality, mídium, writers’ lifestyle, esthetic positioning, enunciation scene, theme, etc.” (MAINGUENEAU, 2016). Therefore, this paper aims to analyze the speech of three female characters that occupy significant roles in Maria da Tempestade (1956), analyzing how the patriarchal speech influences their relations and makes them exercise power.